Facilitative behavioral interactions between deepwater piscivores at Isla del Coco National Park and Las Gemelas Seamount, Costa Rica - Auster, Peter J. (2016)
The shallow waters around Isla del Coco, Costa Rica, have the highest density of apex predators within the Eastern Tropical Pacific. This represents a unique opportunity to assess the structure of predatory interactions in a community relatively unimpacted by fishing. Facilitation of predation has commonly been observed in shallow reef systems, limited in depth by observations via scuba divers. Here we present a preliminary catalog of facilitative behavioral interactions between 12 taxa of deepwater piscivores at Isla del Coco and Las Gemelas Seamount in the Eastern Tropical Pacific, collected via video from submersible vehicles to depths of approximately 311 m from 2002-2012. Observations were ad hoc and likely represent only a portion of the web of interactions that occur in this ecological setting. That such interactions can be observed to 300 m during the narrow time frame of submersible dives suggests that direct behavioral facilitation of piscivory may play a significant role in the apex predator guild of deepwater fishes. Investigating the extent and population-community consequences of such interactions will provide valuable insight into patterns and processes that occur in communities protected from direct fisheries as well as focus conservation actions. Rev. Biol. Trop. 64 (Suppl. 1): S187-S196. Epub 2016 February 01.